Ethnic identity and resilience: a moderated mediation analysis of protective factors for self-blame and racial microaggressions - Barrita, Aldo M.; Wong-Padoongpatt, Gloria (Frontiers in Psychology, 2023)
Introduction: People of Color (PoC) in the United States encounter everyday racial microaggressions, and these commonplace experiences can wear and exhaust PoC’s resources. Racial microaggressions have shown detrimental effects on physical and psychological well-being. Consequently, researchers have examined and tested different ways in which PoC cope and protect themselves from these everyday exchanges. Past findings have indicated that PoC might blame themselves for racism-related occurrences to cope with these commonplace discriminatory experiences. Ethnic identity and resilience have emerged in research as protective factors that can moderate and buffer the impact of racism on PoC’s well-being. We used a combination of mediation, moderation, and conditional analyses to unpack the relationships between racial microaggression (predictor), psychological distress (outcome), self-blame (mediator), resilience (moderator), and ethnic identity (moderator). Methods: This study used a cross-sectional design and sampled 696 PoC regarding their experiences and responses to racial microaggressions. We tested the association between psychological distress and racial microaggressions and further examined whether self-blame mediated the relationship. We also tested ethnic identity and resilience as moderators and used a conditional analysis to determine whether these protective factors moderated the mediation model. Results: Findings from the mediation, moderation, and conditional analyses supported our four hypotheses: (H1) self-blame mediated the relation between racial microaggressions and psychological distress (mediation), (H2) ethnic identity moderated the association between racial microaggressions and self-blame but only at low and average levels (moderation), (H3) resilience moderated the relation between self-blame and psychological distress but only at low and average levels (moderation), and (H4) evidence of moderated mediation were found for all five variables (conditional). While statistically significant, most moderation effects were minimal to small. Conclusion: PoC may engage in self-blame when experiencing racial microaggressions, which explains why these everyday, commonplace occurrences might lead to psychological distress. There was evidence that ethnic identity and resilience can protect PoC from the negative effects of racial microaggressions. These buffering effects, however, only emerged for PoC endorsing high levels of ethnic identity and resilience, and it should be noted that for most participants, the link between racial microaggressions and psychological distress was still significant.